Habitat Restoration Restores Underwater Soundscapes and Larval Recruitment - Butler, Jack; Anderson, Emily R.; Butler, Mark J. (Frontiers in Ecology and Evolution, 2022)
Habitat degradation alters many ecosystem processes, and the potential for the reestablishment of ecosystem function through restoration is an area of active research. Among marine systems, coastal habitats are particularly vulnerable to anthropogenic degradation and, in response, are the focus of marine ecological restoration. One of the crucial functions of structurally complex coastal habitats (e.g., saltmarshes, seagrass meadows, kelp forests, coral reefs) are as nurseries to coastal and offshore species, many of whose larvae utilize sound to locate suitable nursery habitat. However, the effect of habitat degradation and subsequent restoration on underwater soundscapes and their function as navigational cues for larvae is unexplored. We investigated these phenomena in sponge-dominated hardbottom habitat in the waters surrounding the middle Florida Keys (Florida, United States) that have been degraded in recent decades by massive sponge die-offs caused by harmful algal blooms. One of the consequences of sponge die-offs are dramatic changes in underwater sounds normally produced by sponge-associated animals. We tested whether soundscapes from healthy hardbottom habitat influenced larval recruitment, and then examined how hardbottom degradation and restoration with transplanted sponges affected underwater soundscapes and the recruitment of larval fishes and invertebrates. Larval assemblages recruiting to healthy areas were significantly different than those assemblages recruiting to either degraded or restored hardbottom areas. Fewer larvae recruited to degraded and restored areas compared to healthy hardbottom, particularly during the full moon. Experimental playback of healthy hardbottom soundscapes on degraded sites did not promote larval community differences although some individual species responded to the playback of healthy habitat soundscapes. These results indicate that habitat-associated soundscapes have idiosyncratic effects on larval settlement, which is diminished by the degradation of nursery habitat but can be reestablished with appropriate habitat restoration.